Leaders in focus: generational differences from a personality-centric perspective - Bălan, Mădălina; Marin, Silvia; Mitan, Andreea; Pînzaru, Florina; Vătămănescu, Elena-Mădălina; Zbuchea, Alexandra (Management & marketing (Bucharest, Romania), 2019)
The generational differences among leaders have progressively captured the attention of both researchers and practitioners interested in their dynamics within the work environment. Many analyses in this respect have been focused on the differences between Millennials (Generation Y) and Generation X members from a personality-centric perspective, the great majority of the examinations revolving around Western research samples. By acknowledging the current state and assuming the calls for further investigations advanced by various researchers, this conceptual and empirical undertaking aims to provide an exploratory outlook on generational differences among Romanian leaders, by employing worldwide reputed research instruments such as the Hogan Personality Inventory (HPI), Hogan Development Survey (HDS) and Motives, Values, Preferences Inventory (MVPI). A sample of over 700 subjects was considered in the running of the statistical analyses, thus allowing to draw pertinent conclusions apposite to the envisaged population. Even though statistically significant findings were retrieved on few scales pertaining to the three applied instruments, one key insight advanced by the present endeavor resides in the extension of the scope of the existing literature dedicated to the generational differences from a leadership perspective via the integration of an Eastern European landscape which adds to the evidence in the field and opens up new research challenges for complementary scrutiny.